Cytocidal action of homoharringtonine on L1210 cells in vitro - Xu Cheng-xiong; Han Rui (Acta Pharmacologica Sinica, 2016)
The proliferation of L 1210 cells ceased rapidly after they were exposed to homoharringtonine (HH) 1 microgram/ml during exponential growth phase. However, 25.3% of the cells were still able to form colonies in soft agar if HH was removed after 24 h of incubation (the colony-forming efficiency for control cells was 62.5%). The clonogenic cells survived from the treatment were still sensitive to HH-continuous exposure. The IC50 of the treated and control cells were 15 and 20 ng/ml, respectively. Yet, the sensitivity of the treated cells to cytarabine decreased enormously. For instance, the survival rate of HH-treated cells remained at 100% level after they were exposed to cytarabine 4-8 micrograms/ml for 1 h, but only 40% control cells survived from the same treatment. When cells were continuously exposed to HH 0.4 micrograms/ml, the colony-forming efficiency decreased exponentially as a function of exposure time. The T1/2 of the clonogenic cells was about 18 h. The DNA contents in L 1210 cells was measured with a flow-cytometer. The results showed that the cell-cycle progress in all cells was interrupted by HH, regardless which phase they belonged to. So the cells seemed to be in a "frozen" state and the histogram unchanged.